Safety and Efficacy of Brolucizumab in the Treatment of Patients with Diabetic Macular Edema and Diabetic Retinopathy: A Systematic Review and Meta-Analysis - Sharifa N. Bourisly; Fatmah S. Semairan; Yousef Mesaed Al-Shammari; Noor Alali; Lulwa Abbas Alfoudari; Abdulaziz F. Abdulkareem; Abdullah M. Alharran (Journal of Clinical Medicine, 2026)
Background: Brolucizumab is an intravitreal anti-vascular endothelial growth factor (anti-VEGF) agent developed to improve retinal drying and treatment durability in diabetic eye disease. However, its overall efficacy and safety in diabetic macular edema (DME) and diabetic retinopathy remain uncertain because available trials differ in population, comparator, dosing schedule, and follow-up. Methods: We searched PubMed, Cochrane Library, Scopus, and Web of Science from inception to 25 April 2026. Randomized controlled trials evaluating intravitreal brolucizumab in adults with DME, diabetic retinopathy, or proliferative diabetic retinopathy (PDR) were included. Comparators were aflibercept, panretinal photocoagulation, or other active/conventional treatments. The main efficacy outcomes were change in best-corrected visual acuity (BCVA) and central subfield thickness/central subfield foveal thickness (CST/CSFT). Safety outcomes included ocular, non-ocular, serious ocular, and serious non-ocular adverse events. Random-effects meta-analyses were performed. Results: Five reports representing four phase 3 randomized controlled trials were included, enrolling 2132 participants overall; the four-trial primary 6 mg analyses included 1942 participants. Brolucizumab was not associated with a significant improvement in BCVA compared with control treatment (mean difference [MD], 1.21 letters; 95% confidence interval [CI], −1.12 to 3.54; p = 0.3; I2 = 85.1%). However, brolucizumab significantly reduced CST/CSFT (MD −24.45 µm, 95% CI −47.43 to −1.47; p = 0.0370; I2 = 78.2%). No statistically significant differences were detected between groups in the assessed safety outcomes, including ocular adverse events (risk ratio [RR], 0.88), non-ocular adverse events (RR 1.00), serious ocular adverse events (RR 0.63), and serious non-ocular adverse events (RR 0.89). Separate analyses of brolucizumab-specific ocular events showed no statistically significant differences for intraocular inflammation (RR 2.35, 95% CI 0.36–15.42), retinal vasculitis (RR 2.10, 95% CI 0.22–20.10), or retinal vascular occlusion (RR 2.13, 95% CI 0.46–9.87); however, estimates were imprecise because of the small number of events. Conclusions: Across the four included trials, brolucizumab was not associated with a statistically significant difference in BCVA compared with control treatment. In the three DME trials, brolucizumab achieved a greater reduction in CST/CSFT. It may be useful for selected DME patients, while its role in PDR requires longer-term evidence.